The incremental effect of education on corruption: evidence of synergy from lifelong learning - Simplice A. Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2015)
Education as a tool in the fight against corruption has been subject to much debate in academic and policy making circles. This note extends what we know on this nexus in a threefold manner: namely, in terms of: incremental, lifelong learning and synergy effects. Four main findings are established. First, education is a powerful tool in the fight against corruption. Second, there is evidence of an incremental effect in the transition from secondary to tertiary education. Third, lifelong learning defined as knowledge acquired during primary, secondary and tertiary education negatively affects corruption. Fourth, there is evidence of a 'synergy effect' because the impact of lifelong learning is higher than the combined effects of various educational levels. The empirical evidence is based on 53 African countries for the period 1996-2010. Two main policy implications are derived. First, encouraging education through the tertiary level enhances the fight against corruption. Second, the drive towards a knowledge economy by means of lifelong learning has 'corruption mitigating' benefits.
Keywords: I20; I28; K42; O10; O55; 330; Lifelong learning; Corruption; Development; Africa